Soil Biosequences of a Forest Land of Dun Valley with Reference to its Vegetation - Singhal, R. M.; Samra, J. S.; Sharma, S. D.; Pande, P.; Sharma, S. K. (Indian Forester, 1982)
Interrelationship between the soils and vegetation have been discused in respect of a forest land of Dun Valley (U.P.) having sal (Shorea rabusta), teak (Tectona grandis) and miscellaneous species as its main vegetation. The soils under various types of vegetation differ marginally from one another at various levels. The soil under teak and miscellaenous species contain comparatively more available nutrients than soils under sal, which has otherwise sustained greater interaction by vegetation during the course of their development.